APLIKASI LINEANMENT DENSITY ANALYSIS UNTUK MEMBATASI POLA KALDERA PURBA GODEAN - Okki Verdiansyah; Hill Gendoet Hartono (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2017)
Godean area, is an isolated hills that’s occurs on Yogyakarta basin. Volcano occurences in Godean have issued by morphology, lithology and volcanic concepts. Volcanisme and magmatisme on Godean interpreted have similarity with Gajahmungkur – Wonogiri with hydrothermal event occurs. Lineanment Density Analysis used for interpretating the specific pattern, for strength the morphology and geological that have interpreted before. The methods that we used is combining of quantitative and qualitative. Geology of Godean consist of igneous and sedimentary rock with margins of Kulon Progo hill in western side. Caldera morphology, commonly have circular or a half circular pattern, with limited by steep relief. Morphology of Godean have caldera pattern, as a concept and compare with others. LD analysis are using image from slope directional angle processing on SRTM and ASRTER image, and then extract to lineament. Result of lineament extraction there are 9490 lines. Range of density with length from 0 to 9173,21 m/km2 with high value > 2375 m/km2 and count of lineament from 0 to 23 line/km2 with high value > 8 line/km2. Godean have high density with range of length 1930 – 2996 m/km2 or range of counts 9 – 12 line/km2. Base on the pattern, its looks the Godean and surrounding it differ on 3 major sectors, that’s outer rim, secondary rim, and circular of late central eruption. Diameter of this pattern is wide (8 – 15 km), that must be proven with others geological and geophysical subsurface research.